Acoustic analysis and playback experiments do not support the taxonomic revision of the Central and Western Canary Islands subspecies of the Eurasian Stone-curlew Burhinus oedicnemus distinctus. Issue 3 (2nd July 2020) - Dragonetti, Marco; Caprara, Massimo; Rodríguez-Godoy, Felipe; Barone, Rubén; Cerdeña, V. Rubén; Giunchi, Dimitri
ABSTRACT: Capsule: Acoustic analysis does not support the elevation of Central and Western Canary Islands subspecies of the Eurasian Stone-curlew Burhinus oedicnemus distinctus to full species. Aims: To verify whether the vocal repertoires of Eurasian Stone-curlew subspecies oedicnemus and distinctus show biologically significant quantitative and qualitative differences. Methods: We carried out an acoustic analysis of some of the most frequently used call types of Eurasian Stone-curlew, recorded in Italy and in the Canary Islands. Additionally, we used playback experiments to test the response of the two subspecies to calls of their own and the other subspecies. Results: The vocal repertoires of the individuals belonging to the two subspecies were rather similar, but the quantitative analysis of acoustic parameters showed some differences between the populations. In particular, the three most used call types showed higher frequency and faster utterance rhythm for distinctus than oedicnemus . Playback experiments indicated that individuals from the nominate subspecies responded in the same way to the playback of calls of individuals belonging to both subspecies. Conclusion: Acoustic analysis supports the distinctiveness of Eurasian Stone-curlew populations from Central and Western Canary Islands, thus confirming the available morphological and genetic data. These results, however, do not suggest that distinctus should be elevated to a full species.